Self Care Experience of Woman with Breast Cancer - Maha Sari Karolina; Riswani Tanjung; Dudut Tanjung (Indonesian Journal of Global Health Research, 2024)
Breast Cancer treatment not only causes physical but also psychological side effect that will affect Breast Cancer sufferers quality of life. Self care for Breast Cancer sufferers is needed to overcome chemotherapy side effect and help them adapt their condition, so they can improve their quality of life. This research aims to explore experience women with Breast Cancer self care. This research use a qualitative research method with a phenomenological design trough in depth interviews. Participants in this study were 12 women who were diagnosed with Breast Cancer and had undergone chemotherapy. The data analysis process in this research uses the Colaizzi analysis method. The results of data analysis from this research revealed 5 themes, seeking information and treatment at the start diagnosis, adaptation process after receiving treatment, support during chemotherapy, obstacle in carrying out treatment and hope in breast cancer treatment. Women who are diagnosed with breast cancer make various efforts to overcome their disease starting from the first symptoms discovered until the treatment process is undertaken with various obstacles and perceived support, this is done because they have high hopes for recovery in the future.